Nursing workload in a trauma intensive care unit - Luana Loppi Goulart; Roberta Nazário Aoki; Camila Fernanda Lourençon Vegian; Edinêis Brito Guirardello (Universidade Federal de Goias, 2014)
Severely injured patients with multiple and conflicting injuries present themselves to nursing professionals at critical care units faced with care management challenges. The goal of the present study is to evaluate nursing workload and verify the correlation between workload and the APACHE II severity index. It is a descriptive study, conducted in the Trauma Intensive Care Unit of a teaching hospital. We used the Nursing Activities Score and APACHE II as instruments. The sample comprised 32 patients, of which most were male, young adults, presenting polytrauma, coming from the Reference Emergency Unit, in surgical treatment, and discharged from the ICU. The average obtained on the Nursing Activities Score instrument was 72% during hospitalization periods. The data displayed moderate correlation between workload and patient severity. In other words, the higher the score, the higher the patient's mortality risk. doi: 10.5216/ree.v16i2.22922.